1998
DOI: 10.1146/annurev.biochem.67.1.99
|View full text |Cite
|
Sign up to set email alerts
|

MODIFIED OLIGONUCLEOTIDES: Synthesis and Strategy for Users

Abstract: Synthetic oligonucleotide analogs have greatly aided our understanding of several biochemical processes. Efficient solid-phase and enzyme-assisted synthetic methods and the availability of modified base analogs have added to the utility of such oligonucleotides. In this review, we discuss the applications of synthetic oligonucleotides that contain backbone, base, and sugar modifications to investigate the mechanism and stereochemical aspects of biochemical reactions. We also discuss interference mapping of nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
190
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 300 publications
(194 citation statements)
references
References 286 publications
0
190
0
2
Order By: Relevance
“…The phosphorothioate method provides a tool for the analysis of function, structure, and interactions of nu- cleic acids with atomic resolution (Eckstein, 1985;Verma & Eckstein, 1998)+ R p -phosphorothioates are statistically incorporated 59 to one of the four bases by T7 in vitro transcription+ Every single substitution can be mapped by separation of the iodine cleavage products on a sequencing gel+ The use of phosphorothioate analogs broadens the applicability of the method in that information about other atomic groups than the phosphate residue are generated (Strobel, 1999)+ The in-gel cleavage approach presented here is an extension to the well-established probing techniques+ It opens the possibility of monitoring assembly steps of multimolecular complexes, if they can be separated by PAGE+ RNP complexes in native polyacrylamide gels behave as in solution+ For example, in a DNA-RNA polymerase system, it was shown that on-and off-rates are identical to those in solution (Revzin et al+, 1986); the same observation holds true for a ribosomal RNAprotein system (Draper et al+, 1988)+ Therefore structural probing within native gels gives reliable information about the solution structure+…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorothioate method provides a tool for the analysis of function, structure, and interactions of nu- cleic acids with atomic resolution (Eckstein, 1985;Verma & Eckstein, 1998)+ R p -phosphorothioates are statistically incorporated 59 to one of the four bases by T7 in vitro transcription+ Every single substitution can be mapped by separation of the iodine cleavage products on a sequencing gel+ The use of phosphorothioate analogs broadens the applicability of the method in that information about other atomic groups than the phosphate residue are generated (Strobel, 1999)+ The in-gel cleavage approach presented here is an extension to the well-established probing techniques+ It opens the possibility of monitoring assembly steps of multimolecular complexes, if they can be separated by PAGE+ RNP complexes in native polyacrylamide gels behave as in solution+ For example, in a DNA-RNA polymerase system, it was shown that on-and off-rates are identical to those in solution (Revzin et al+, 1986); the same observation holds true for a ribosomal RNAprotein system (Draper et al+, 1988)+ Therefore structural probing within native gels gives reliable information about the solution structure+…”
Section: Discussionmentioning
confidence: 99%
“…The RNA structure within ribonucleo-protein particles (RNPs) might deviate strongly from that observed with free RNA+ For example, the ribosomal assembly runs through a series of intermediate particles with increasing S-values+ Thus, the folding process leads to particles of increasing compactness during the course of assembly involving conformational changes of the rRNA, although the number of proteins present in the intermediates successively formed goes up (for review see Nierhaus, 1991)+ The structural changes of the rRNAs during the assembly process are an interesting issue, but suitable techniques to study this issue are rare+ It is prohibitively difficult to follow the folding process by X-ray analysis, because the intermediate particles have a looser structure than the mature particle, thus impeding the formation of crystals+ Likewise, NMR methods cannot be applied, because complexes involving more than three RNA or protein components are usually too large to be analyzed+ Digestion experiments of the RNPs with RNases specific for single or double strands are not informative, because internal RNA regions are not accessible to the enzymes+ Hydroxyl radicals or reagents that modify bases in single-stranded regions are small enough to penetrate a complex and to give valuable information about RNA binding sites of proteins+ These techniques have been successfully applied for the assembly of the small subunit of the Escherichia coli ribosome (Powers et al+, 1993;Powers & Noller, 1995), where proteins were added one by one according to the 30S assembly map+ Nucleotides that were accessible in the preceding assembly step but became protected upon addition of the next protein allowed conclusions about the effects of this protein+ Another important technique is the phosphorothioate technique (Verma & Eckstein, 1998;Strobel, 1999), where modified RNAs that contain a sulfur atom in-stead of a nonbridging oxygen at the phosphate residues are used+ The small inert iodine can trigger a cleavage of the phosphate-sugar backbone at the modified phosphate residue (Gish & Eckstein, 1988) and thus probe the structure based on accessibility+ The advantage of this method is that it works equally well in single-and double-stranded RNA regions; in addition the modified RNA usually has full biological activity, as demonstrated for thioated tRNAs (Rudinger et al+, 1992;Dabrowski et al+, 1995)+ In some cases the incorporation of single thioated nucleotides prevents, for example, formation of an RNAprotein complex+ A reason could be that either a phosphorothioate at this position can induce a change of the RNA structure that prevents binding (Smith & Nikonowicz, 2000) or the unmodified phosphate at this position is essential for complex formation+ This experimental strategy to identify residues essential for binding is called interference strategy, because modifications that interfere with the complex formation are identified+ The remaining majority of nucleotides do not interfere with complex formation and thus can be analyzed in a second strategy of this method, namely, the protection approach+ Here the extent of protection against iodine cleavage by the proteins in complex with RNA can be assessed thus revealing contacts with the respective phosphate residues+…”
Section: Introductionmentioning
confidence: 99%
“…Nucleotide bases have been recognized as identity elements in interaction of tRNAs with synthetases (Normanly & Abelson, 1989;Söll & RajBhandary, 1995)+ 29-Hydroxyl groups have also been shown to play a role in this process+ These experiments were based on a complete exchange of all 29-deoxy groups in the molecule (Khan & Roe, 1988) or just one of the four nucleotides (Aphasizhev et al+, 1997)+ Additionally, kinetic analysis of single 29-deoxy-modified positions in minihelices or tRNA fragments of tRNA Ala or tRNA Pro showed small but distinct effects in aminoacylation efficiency (Musier-Forsyth & Schimmel, 1992;Yap & Musier-Forsyth, 1995)+ We were interested in an in vitro scanning procedure which should rapidly identify such 29-deoxy-sensitive sites in a complete tRNA rather than testing individual positions in a stepwise fashion+ The E. coli tRNA Asp system was chosen because it offered the opportunity to compare the results with an X-ray structural model still under final refinement (L+ Moulinier & D+ Moras, pers+ comm+)+ Although the simplest method for scanning a tRNA for the importance of 29-hydroxyl groups for aminoacylation should be the random incorporation of 29-deoxynucleotides, the identification of the interfering positions by limited alkaline hydrolysis proved impractical in our system because of high background of cleavage, even though this procedure had been applied to a 15-nt-long tRNA anticodon stem-loop fragment to test ribosomal A site binding (von Ahsen et al+, 1997)+ We therefore chose to couple the 29-deoxy modification with a phosphorothioate modification that generates a signal only at the deoxy positions upon iodine cleavage (Gish & Eckstein, 1988) and thus facilitates the 29-deoxy identification+ As any interference observed with this double modification could result from the deoxy and/or the phosphorothioate substitutions, the effect of the phosphorothioate modification was determined separately by transcribing the E. coli tRNA Asp with dNTPaS or NTPaS+ Both pools were then charged with the cognate synthetase and a tRNAs were ligated using one unmodified half and one half containing the deoxynucleotide at the identified position as described in Materials and Methods+ Each measurement was repeated at least twice+ Error Յ 20%+ (Gish & Eckstein, 1988;Schatz et al+, 1991;Verma & Eckstein, 1998)+ Because the incorporation of the analogues is random, this approach does not rely on any assumption about which positions might be important and thus differs from the previous studies+ In the scanning experiments positions U11, A24, U25, C28, U29, C36, C48, G57, A58, and C67 showed only a deoxy effect+ All others were accompanied by considerable phosphorothioate interference+ At G34, C74, and C75 the deoxy effect on top of the phosphorothioate interference was considered strong enough to be indicative of an additional effect+ The only position where the phosphorothioate effect was stronger than the deoxy effect was U35, the central position of the anticodon+ However, in general, comparison between these two effects is made difficult by the fact that the amount of dNTPaS and NTPaS incorporation is not necessarily the same+ The assignment of deoxy effects was therefore conservative+…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are unsuitable as systemic therapeutics because they bind weakly to plasma proteins and are rapidly filtered by the kidney. These issues can be overcome by chemical modifications of the phosphodiester backbone, of the purine and pyrimidine heterocyclic bases, and of the sugar moiety [3,4]. Phosphorothioate (PS)-containing oligonucleotides, where one of the nonbridging phosphate oxygen atoms is replaced by one sulfur atom, were one of the earliest and currently most widely used backbone modifications of oligonucleotide molecules [5].…”
Section: Introductionmentioning
confidence: 99%